Reliability and Factorial Structure of the Farsi Version of the Arabic Scale of Death Anxiety in an Iranian Middle-Aged Sample - Dadfar, Mahboubeh; Bahrami, Fazel (The Scientific World Journal, 2016)
The present study aimed to explore the psychometric properties of the Arabic Scale of Death Anxiety (ASDA) in an Iranian middle-aged sample. A sample of 55 volunteer Iranian persons took part in the study. Cronbach’s alpha of the ASDA was found to be high (0.91) and Spearman-Brown and Guttman Split-Half coefficients were 0.86. The factor analysis of the ASDA items yielded five factors accounting for 72.49% of the total variance and labeled (F1) fear of death and fear of dead people; (F2) fear of postmortem events and fear of tombs; (F3) fear of lethal disease; (F4) preoccupation with after death, and death fear in sleep; and (F5) fear of deprivation of own ones. The ASDA has a good validity and reliability, and it can be used in clinical, educational, and research settings.